Cover Picture: Ultrabright Lanthanide Nanoparticles (ChemPlusChem 6/2016). Issue 6 (30th March 2016) - Goetz, Joan; Nonat, Aline; Diallo, Abdoulaye; Sy, Mohamadou; Sera, Ildan; Lecointre, Alexandre; Lefevre, Christophe; Chan, Chi Fai; Wong, Ka‐Leung; Charbonnière, Loïc J.
Abstract : The cover picture shows terbium‐doped LaF3 nanoparticles that are surface functionalized by photon‐harvesting antenna ligands. Surface capping with antenna ligands leads to ultrabright nanoparticles, with the typical green luminescence signature of the Tb atoms and very long excited state lifetimes. The nanoparticles were shown by luminescence microscopy to internalize into HeLa cells and localize to the lysosomes. Details are given in the Full Paper by Loïc J. Charbonnière and Ka‐Leung Wong et al. onpage 526 in Issue 6, 2016 (DOI:10.1002/cplu.201600007 ).